(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Crimean-Congo hemorrhagic fever (CCHF) is a fatal viral infection with a mortality rate of 10 to 40% when transmitted by ticks and up to 80% when acquired through hospitalization. Human cases have been reported in more than 30 countries across Europe, Asia, and Africa. Rapid and accurate diagnosis of CCHF is essential for appropriate treatment, predicting the outcome, and preventing further spread of the infection. Molecular methods such as polymerase chain reaction (PCR) have been widely used in infectious diseases. The aim of this study was to develop new primers and probes for the rapid and specific detection of CCHF virus RNA using a one-step real-time RT-PCR assay. Following optimization and laboratory testing, the developed oligonucleotides could enable effective detection of CCHF virus in clinical samples.